Brillouin Optomechanics: Strong coupling, the lasing transition, and single-phonon-level operations - Vanner,MR (2024)
Backward Brillouin scattering in whispering-gallery-mode micro-resonators offers an exciting avenue to pursue both classical and quantum optomechanics applications. Our team—the Quantum Measurement Lab—together with our collaborators, are currently exploring and utilizing the favourable properties this platform affords for non-Gaussian motional state preparation of acoustic fields. In particular, the high acoustic frequencies, acoustic mode selectivity, and low optical absorption provide a promising route to overcome current hindrances within optomechanics. Some of our key recent results in this direction include: the observation of Brillouin optomechanical strong coupling, single-phonon addition and subtraction to a thermal state of the acoustic field, advancing the state-of-the-art of mechanical state tomography to observe the non-Gaussian states generated by single- and multi-phonon subtraction, studying the second-order coherence across the Brillouin lasing threshold, and enhancing sideband cooling via zero-photon detection. This talk will cover these results, what they enable, and the broader direction of our lab.